Adsorption Studies of Ca2+ Ions on α-Fe2O3 Dispersed Natural Rubber Composite: Structure, Morphology and Thermal Studies - V. HAVANOOR, VIJAYANAND; MALLIKARJUNA, N.N.; KUMAR LAGASHETTY, ARUN; VENKATARAMAN, A. (Asian Journal of Chemistry, 2010)
Ultrafine particles of α-Fe2O3 dispersed natural rubber composite film prepared by solvent casting method are reported. The prepared film is subjected to Ca2+ ions adsorption. The adsorbent is characterised with XRD, SEM and thermal studies. The eluent is estimated for Ca2+ ions by EDTA complexometric titration and the results are compared before adsorption. The solution state conductivity shows increase in conductivity due to decrease in concentration of Ca2+ ions.